FACILE PHOTOMETRIC DETERMINATION OF SILVER WITH 2,4,5,7-TETRAIODOFLUORESCEIN STABILIZED WITH STARCH - Erik Prasetyo (Pusbindiklat - LIPI, 2013)
Simple photometric determination of silver was developped. The determination incorporated 2,4,5,7-tetraiodofluorescein (erythrosine) as chromogenic reagent to form positive colloid with silver ion, not ion associate as initially assume. The colloid was then stabilized with starch and this ternary system erythrosine-silver-starch was applied as basis in determination of trace amount of silver (0–6 µg/ml). The developped method was successfully applied to determine silver in three synthetic samples and came with accuracy > 96.87% after compared to atomic absorption spectrophotometry (AAS) results and reproducibility < 8.8%.